International Chambers of Commerce as an Alternative Institution for Resolving Contractual Disputes Generator Independent Power Produce - Widiatmoko, Ndaru Seto; Sami'an, Sami'an; Hardjomuljadi, Sarwono (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
The provision of electricity has a very important and strategic role in realizing national development in Indonesia. PT PLN (Persero) as a State-Owned Enterprise (BUMN) which in the law is given the mandate in the provision of electricity carries out its role in the business of providing electricity, one of which is the construction of power plants. In the provision of electricity through the construction of power plants, PT PLN (Persero) can appoint a private company to become the developer of the Independent Power Produce (IPP) plant construction with a power purchase agreement scheme whose provisions are regulated by the Regulation of the Minister of Energy and Mineral Resources. In this study, we will analyze the dispute resolution mechanism in the agreement contract of PT. PLN (Persero) with PT. Poso Energy in the supply of electricity for the Poso hydropower plant through the International Chamber of Commerce. The method used in this study is the normative juridical method in the statute approach and the qualitative analysis method in the example of the Poso IPP hydropower contract to get an overview of the conclusion of the alternative dispute resolution chosen by the parties by paying attention to the applicable legal foundations and concepts in the dispute resolution of construction contract agreements.